RECURRENT ISCHEMIC STROKE IN ELDERLY WITH POLYCYTHEMIA VERA: CASE REPORTA - Pradita Sri Mitasari; Setyawati Setyawati (Berkala Ilmiah Kedokteran Duta Wacana, 2023)
Background: Myeloproliferative disorders can rise a risk of thrombotic events. Ischemic stroke is one of presenting symptoms can be found in such patients. These coexisting conditions can burden patients with more severe complications.Objectives: To discuss a case of polycythemia vera with multiple episodes of ischemic stroke.Case description: The patient was a 70-year-old female with chief complaint of sudden rotatory dizziness with moderate to severe intensity. Nausea, vomiting, slurred speech, and facial muscle weakness were also reported. Onset of symptoms started 3 hours before hospital admission. Medical history including previous ischemic stroke in 2020 and 2015 with remaining right extremity weakness. Physical examination showed weakness, hypertension. Nystagmus horizontal bidirectional and upper motor neuron lesion of left CN VII and XII, weakness in right upper and lower extremities were observed. Physiological reflexes were increased, and pathological reflex was found. Head CT showed hypodense lesion led to her ischemic stroke diagnosis. Blood test showed increased hemoglobin count, leukocytosis but normal platelet count. Increased cell numbers and variations of size, morphology and distribution were found in peripheral smear. This finding was also supported with bone marrow examination which showed hypercellularity, panmyelosis with dysplasia of all hematopoietic lineage. Patient was diagnosed with polycythemia vera and treated accordingly.Conclusion: Further examination of hematology, such as peripheral smear or bone marrow examination should be considered in patients with recurrent episodes of stroke to rule in underlying myeloproliferative disorders.Appropriate treatment and routine hematology follow up are in need to increase awareness of future thrombotic events or leukemic transformations.